A Bioinformatic Approach to the Bioprospecting of Plastic Waste Degrading Enzymes (Chemical Engineering Research Bulletin, 2026)
Plastic waste pollution poses a major threat to environmental sustainability, and the biochemical degradation of plastics through enzymatic processes offers an attractive and viable solution to this menacing problem. However, identifying suitable plastic degrading enzymes is a significant challenge. Traditional bioprospecting methods such as high-throughput enzyme screening, although identified several experimentally validated enzymes, are largely unsuccessful, time consuming, and expensive. Bioinformatics can offer a cheaper, quicker, and more successful approach to bioprospecting of novel plastic degrading enzymes. This study describes the development of an automated bioinformatics pipeline to identify proteins homologous to a query protein using a range of criteria, including sequence similarity, evolutionary relationship, and structural alignment. Using the sequences of known plastic degrading enzymes as input, the pipeline identified four homologous proteins with a high potential for plastic degrading functionality: Lipase, Lipase 1, and two uncharacterized esterases, XCC2094 and ATU5261. These proteins and the microorganisms which produce them can be tested in vitro to confirm their plastic degrading abilities, with the aim of identifying microorganisms capable of degrading all the seven types of plastics, or simply providing better plastic degrading capabilities.Chemical Engineering Research Bulletin: 24 (Issue 1): 1-12